Enhancing the Supersonic Wind Tunnel Performance Based on Plenum Temperature Control. (1st April 2014) - Nazarian Shahrbabaki, A.; Bazazzadeh, M.; Shahriari, A.; Dehghan Manshadi, M.
Abstract : The application of fuzzy logic controllers (FLCs) to the control of nonlinear processes, typically controlled by a human operator, is a topic of much study. In this paper, the design and application of a FLC is discussed to control the plenum chamber temperature for a blowdown supersonic wind tunnel (BSWT) with the aim of achieving the accurate and desired results. In this regard, first, a nonlinear mathematical model of special BSWT is developed in Matlab/Simulink software environment. Next, an artificially intelligent controller is designed using fuzzy logic approach. For this purpose, a proportional-derivative FLC (PD-FLC) system is developed in the Simulink toolbox to control the plenum stagnation temperature using a heater upstream of the plenum chamber. Finally, the system simulation results inside of the temperature and pressure controllers in comparison with the experimental run are presented. The results for Mach 2.5 blowdown run show the great performance of the Wind Tunnel Simulator Model and its temperature controller system.